P110 The role of TB chemoprophylaxis in renal transplant recipients. (15th November 2016) - Periselneris, JN; Mahendran, S; Chowdhury, P; Milburn, H
Abstract : Background: Rates of tuberculosis infection are increased after solid organ transplant. This is associated with increased mortality and allograft loss in one third of cases. The WHO recommend testing for latent tuberculosis (LTBI) in patients receiving dialysis or preparing for solid organ transplant. BTS and ERS guidelines suggest screening for LTBI where tuberculosis incidence rates are high or in patients with risk factors for developing tuberculosis in low incidence areas. They go on to propose chemoprophylaxis with isoniazid or three months of rifampicin and isoniazid, with above 60% effectiveness at preventing subsequent tuberculosis. Guidelines at a large renal transplant centre advocate isoniazid prophylaxis for 6 months post transplant in all patients of Indo-Asian or African heritage as well as anyone who is from a country with TB incidence rates above 40/100, 000 who have been in the UK for less than 5 years. Methods: All patients who underwent renal transplantation between January 2011 and December 2014 were assessed to see if tuberculosis prophylaxis was prescribed as per guidelines. Cases of subsequent TB were then identified. Results: 912 patients underwent renal transplant during this time. 243 (26.6%) received isoniazid prophylaxis, with 88% adherence to trust guidelines. 42 (4.6%) patients who should have received prophylaxis did not. During this time one patient developed tuberculosis post transplant. This individual should have received isoniazid according to guidelines, but did not. Another patient from sub-Saharan Africa was discovered to have abdominal tuberculosis when on the operating table prior to transplant. Discussion: We are not aware of any LTBI screening programme amongst renal transplant units in the UK currently. Many use prophylactic isoniazid in a similar manner to our trust. Pre-emptive screening with interferon gamma release assays costs approximately £60 per test, 6 months of isoniazid £560 and 3 months of rifampicin and isoniazid costs £185. Whilst screening may reduce overall costs and may identify patients earlier, protocol based isoniazid prophylaxis is effective in preventing active tuberculosis. Conclusion: While Isoniazid prophylaxis was effective in prevention of subsequent tuberculosis, screening prior to transplantation should have identified both patients who developed TB.